Metagenomic analysis of gut microbiota and antibiotic-resistant genes in Anser erythropus wintering at Shengjin and Caizi Lakes in China - Liu, Gang; Xu, Na; Feng, Jiahui (Frontiers in Microbiology, 2023)
Migratory birds are the primary source and reservoir of antibiotic-resistant genes (ARGs) related to their gut microbes. In this study, we performed metagenomics to analyze the gut microbial communities and ARGs of Anser erythropus wintering at Shengjin and Caizi Lakes. The results showed that bacteria, fungi, viruses, and archaea were the dominant gut microbes. Principal component analysis (PCA) indicated that the microbiota compositions significantly differed between the two populations. Diet may be the most crucial driver of the gut microbial communities for A. erythropus. This species exclusively fed on Poaceae spp. st Shengjin Lake and primarily on Carex spp. at Caizi Lake. The dominant resistant types were tetracycline, macrolide, fluoroquinolone, phenicol, and peptide antibiotics. ARGs had a significantly higher abundance of operational taxonomic units (OTUs) from Shengjin Lake samples than those from Caizi Lake samples. PCA analysis indicated that most Shengjin Lake samples differed significantly in gut microbiota composition from those at Caizi Lake. This was attributed to extensive aquaculture operations and poultry farms around Shengjin Lake than those around Caizi Lake. ARGs-microbes associations indicated that 24 bacterial species commonly used as indicators of antibiotic resistance in surveillance efforts were abundant in wintering A. erythropus. Results revealed the composition and structural characteristics of the gut microbiota and ARGs of A. erythropus, pointing to their high sensitivity to diet habits at both lakes. This study also provides primary data for public health risk prevention and control of potential pathogens, which are of great significance to epidemiological and public health.